The Triad of User Satisfaction: Lifestyle, Convenience, and Trust in OVO: Dampak Gaya Hidup, Kemudahan, dan Kepercayaan terhadap Kepuasan Pengguna: Studi pada Pengguna Aplikasi OVO - Farikha Nur Mafulah; Dewi Komala Sari (Academia Open, 2022)
This research aimed to investigate the influence of lifestyle, convenience, and trust on the satisfaction of OVO application users in Sidoarjo. The study employed a quantitative approach, collecting data from a sample of 100 respondents. IBM SPSS version 25 software was utilized for data analysis, encompassing validity and reliability tests, as well as various classical assumption tests. Multiple linear regression analysis was employed to examine the relationships between the variables. The findings revealed that lifestyle, convenience, and trust significantly affected consumer satisfaction both individually and collectively. The outcomes of this study contribute to our understanding of the factors influencing user satisfaction in digital payment applications. The implications of this research highlight the importance of catering to users' lifestyles, providing convenience in transactions, and fostering trust to enhance satisfaction levels in similar electronic payment platforms. Highlights: Lifestyle, Convenience, and Trust: This study examines the impact of lifestyle, convenience, and trust on user satisfaction in the context of the OVO application. Understanding how these factors influence satisfaction can help improve the overall user experience. Quantitative Data Analysis: The research employs a quantitative approach, utilizing data processing assistance from IBM SPSS version 25 software. This allows for rigorous analysis of the collected data, providing valuable insights into the relationships between variables. Implications for Digital Payment Platforms: The findings of this study have practical implications for digital payment platforms, emphasizing the significance of catering to users' lifestyles, ensuring convenience in transactions, and fostering trust. Implementing strategies based on these factors can enhance user satisfaction and drive success in the competitive digital payment market. Keywords: Digital payments, User satisfaction, Lifestyle, Convenience, Trust